Merokok Membunuhmu: Kajian Ambiguistik dan Etika dalam Pendidikan Islam - Adi, Nugroho Prasetya; El Syam, Robingun Suyud (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
The message that smoking will kill you seems scary and scary, but the end result is that people are increasingly enthusiastic about consuming it. This article aims to examine smoking kills you: ambiguous studies and Islamic ethics, which previous research has not discussed. Research is a literature review from journal and book sources, then analyzed qualitatively. Research results: that the message that smoking kills you is ambiguous, where on the one hand the government prohibits it because cigarettes are dangerous to health, on the other hand cigarettes are a large source of state income from excise tariffs. From the perspective of Islamic ethics, smoking must pay attention to environmental aspects for comfort, where Islam upholds the rights of other people. This research contributes to future research directions in the field of Islamic ethics. The research synergizes the prominent ambiguous aspects and the importance of Islamic ethics in behavior.